The understanding by design guide to creating high-quality units - Wiggins, Grant P.; McTighe, Jay.; Gale Group (Alexandria, Va. ASCD, 2011)
This book focuses on the basic concepts behind the Understanding by Design approach used by educators to create classroom curriculum that focus on students' understanding of important ideas and working backwards from there. Contains eight modules that are based on a typical workshop presentation, which can also be studied out of sequence, intended for K-16 educators.
Module A : the big ideas of UbD--Module B : the UbD template--Module C : starting points--Module D : developing an initial unit sketch--Module E : different types of learning goals--Module F : essential questions and understandings--Module G : determining evidence of understanding and developing assessment tasks--Module H : learning for understanding.
Electronic reproduction.
Keywords: Curriculum planning -- United States; Curriculum-based assessment -- United States; Learning; Comprehension; Electronic books